The translation and adaptation of the malay version of the absorption in musical responsiveness scale (AIMS) and ollen musical sophistication index (OMSI): a preliminary study - Man, Tan Cheng (2015)
The suitability of musically-based speech and language therapy can differ based on individual differences in musical responsiveness. Although musicians notably differ from non-musicians in musical responsiveness, classification of these two categories are also inconsistent. This study addresses the gap in assessing musical responsiveness and musical aptitude/ability by adopting and translating their original English assessment questionnaires to the Malay language. The Absorption In Musical Responsiveness Scale (AIMS) measures one’s emotional susceptibility to music (musical responsiveness) and the Ollen Musical Sophistication Index (OMSI) measures one’s musical aptitude and ability (musical sophistication). Malay translations of both questionnaires are necessary for its utility in determining the role of music in communication disorders and improving diagnosis, particularly among the predominantly Malay population in Malaysia. Translations consisted of standard forward and backward translations with an assembled expert panel. Content validity was measured by Content Validity Index (CVI) values, which assessed item relevancy in questionnaires. Face validity was determined by administering the questionnaires on 10 fluent Malay-speaking participants and their responses on the suitability and usability of both questionnaires in the debriefing forms. Internal consistency reliability was measured from another 39 participants with Cronbach’s alpha value using IBM Statistical Packages for Social Science (SPSS) Version 22. Content validity was high for both AIMS (0.95) and OMSI (0.98) questionnaires. Face validity was good as all participants found both questionnaires clear, suitable and understandable. Cronbach’s alpha value AIMS (0.928) and OMSI (0.675) were also satisfactory. Thus, the Malay AIMS and OMSI questionnaires demonstrated good content and face validity comparable with their original versions and satisfactory internal consistency reliability. This study provides the preliminary basis for subsequent validation studies and its utilization in control and communication disordered populations, facilitating the efficacy of musically-based therapy in speech and language interventions.